A new intertidal species of the thorid shrimp genus Heptacarpus Holmes, 1900 (Decapoda: Caridea) from Japan - Komai, Tomoyuki (Zootaxa, 2023)
A new species of the thorid shrimp genus Heptacarpus Holmes, 1900, H. sadoi, is described and illustrated on the basis of six specimens from the southeastern coast of the Boso Peninsula, central Japan. All the specimens were collected from intertidal tide pools at low tide. Heptacarpus sadoi n. sp. belongs to the species group with epipods on the pereopods 1–3 and appears morphologically close to H. jordani (Rathbun, 1902) known from Japan and Korea. The new species is readily differentiated from H. jordani by the short rostrum with fewer dorsal teeth and the possession of only one spine on the distal margin of the basal article of the antennular peduncle. Genetic comparison using two mitochondrial markers (COI and 16S rRNA genes) also supports that the new taxon is distinct from H. jordani.